Satisfaction Level of Old Age Allowance Receiving Elderly People in Kushma Municipality - Aryal, Vijay; Paudel, Bhanu Bhakta (Journal of Political Science, 2021)
This paper discusses the contribution and effectiveness of old age allowance among the elderly people and also comes up with the factors associated with the satisfaction level of old age allowance. A cross sectional descriptive study was carried out among 136 elderly people receiving old age allowance in Kushma Municipality, Parbat. The information was collected from people aged 60 years and above through interviews using semi-structured questionnaires. The blend of qualitative and quantitative data was employed for the study. The majority of the elderly population was in the age group of 70-75 years with 68 percent elderly people illiterate. The result shows a significant association of the level of satisfaction of the allowances received with the physical infrastructure and socio-economic development regardless of age, gender and caste/ethnicity. This gives an impetus for making policies and programmes for the elderly in order for them to live with happiness and satisfaction.